A Design Guide for Worship Spaces at Home: Exploring the Influence of Extrinsic Motivation on Intrinsic Motivation in Worshipping - Hadi Jaya Putra; Aulia Fikriarini Muchlis; Hanson Endra Kusuma (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2024)
This research investigates the influence of extrinsic motivation on intrinsic motivation during worship at home and its implications for designing worship spaces within residential settings. The study explores the interplay between extrinsic and intrinsic motivations by employing a mixed-method approach, including qualitative and quantitative methods such as sequential mixed methods and factor analysis. The findings reveal that extrinsic motivation significantly shapes intrinsic motivation during worship at home. The research highlights the significance of privacy in fostering intrinsic motivation during home worship, where private spaces create a conducive environment for individuals to attain solemnity in their worship. In contrast to public spaces like mosques, designing dedicated worship spaces at home becomes essential to ensure a disturbance-free and enhanced worship experience. In conclusion, this study provides valuable insights into the relationship between extrinsic and intrinsic motivations during worship at home. The identified tranquillity, spatial comfort, privacy, and spatial dimension can serve as essential considerations in designing worship spaces to enrich the worshippers' solemn experience within residential settings by architects or designers.